2007
DOI: 10.1021/bi701193x
|View full text |Cite
|
Sign up to set email alerts
|

d-Glucose-Recognition and Phlorizin-Binding Sites in Human Sodium/d-Glucose Cotransporter 1 (hSGLT1):  A Tryptophan Scanning Study

Abstract: In order to gain a better understanding of the structure-function relation in hSGLT1, single Trp residues were introduced into a functional hSGLT1 mutant devoid of Trps at positions that previously had been postulated to be involved in sugar recognition/translocation and/or phlorizin binding. The mutant proteins were expressed in Pichia pastoris, purified, and reconstituted into liposomes. In transport experiments the putative sugar binding site mutants W457hSGLT1 and W460hSGLT1 showed a drastic decrease in af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 70 publications
2
39
0
Order By: Relevance
“…The side view helix H1 is shown to illustrate the positioning of Pz with regards to aglucone and gluoside binding pockets. Such interaction leads to a condensed state of loop 13 followed by major conformational changes [10], similar to what has been observed in the intact human SGLT1 carrier [22]. Evidence for specific conformational arrangements of the aglucone binding site was also obtained in AFM studies on intact cells [23].…”
Section: Model Of Pz Interaction With Sglt1-loop 13supporting
confidence: 71%
“…The side view helix H1 is shown to illustrate the positioning of Pz with regards to aglucone and gluoside binding pockets. Such interaction leads to a condensed state of loop 13 followed by major conformational changes [10], similar to what has been observed in the intact human SGLT1 carrier [22]. Evidence for specific conformational arrangements of the aglucone binding site was also obtained in AFM studies on intact cells [23].…”
Section: Model Of Pz Interaction With Sglt1-loop 13supporting
confidence: 71%
“…Human SGLT1, encoded by the SLC5A1 gene on chromosome 22q13.1, is a 664-amino-acid protein, which contains 14 transmembrane α-helical domains [5, 22]. The glucose-binding domain of human SGLT1 is supposed to include amino acid residues 457-460 [23]. SGLT1 has a high-affinity for glucose (K 0.5 of 0.5-2 mM) and transports sodium and glucose with a 2:1 stoichiometry which enhances its concentrating power [5, 23-25].…”
Section: Molecular Nature Of Sglt1mentioning
confidence: 99%
“…Panayotova-Heiermann et al (16,17) have shown that the C-terminal half of the protein is responsible for D-glucose binding and translocation. Several mutagenesis studies and tryptophan scanning analysis of the isolated transporter have identified a variety of amino acids in the transmembrane helix between aa 454 and aa 460 (18,19). There is also evidence from single molecule recognition studies on brush border membrane vesicles using PAN3-2-poised cantilevers that D-glucose interacts with loop 13 of the transporter.…”
Section: * This Work Was Supported By Austrian Science Fund Project Fmentioning
confidence: 99%
“…In previous studies we have shown that phlorizin binds to loop 13 of rabbit SGLT1 (aa 541-638) via the aromatic aglucone moiety inducing conformational changes of the loop, predominantly in the region between aa 600 and aa 621 (4,6) of the C terminus. Mutagenesis experiments provided also data on individual amino acids critically important for the interaction with the inhibitors (6,13,14).…”
mentioning
confidence: 99%